Transaktionskostentheoretisch basierte Analyse der Organisationsprobleme bei der Erschließung des Ok̈omarktes - Wolfram Dienel (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– An analysis of organizational problems in markets for organic products based on transaction cost economics: Market extension for organic products is restricted due to three types of organizational problems: (1) problems on resourcing (limited supply), (2) deficits in market structure and (3) problems of safeguarding special (pioneer) investment against opportunism. The market of organic products is characterized by high asset specificity and uncertainty of transactions. Solving problems of safeguarding will be the crucial issue if organic markets shall be extended on large scale. Safeguarding is not only achieved by vertical integration but as well by market-driven forms of organization if balancing factors such as equilibrium of asset specificity between market partners, their reputation and relational marketing prevent opportunism. The exact analysis of transaction dimensions and of their balancing powers provides the basis for a market-driven safeguarding-system in the organic market, which offers often a more efficient management of safeguarding than vertical integration. In this way there can be build up a vertical cooperation (strategic alliance) without hierarchy.
Keywords: 330; Bio-Lebensmittel; Ökologischer Landbau; Marketing; Transaktionskosten